Experience of the Varicella Vaccine Introduction into Regional Vaccination Shedule of the Russian Federation - M. A. Baryshev; O. P. Chernyavskaya; T. S. Saltykova (Эпидемиология и вакцинопрофилактика, 2020)
Subject. Varicella continues to be a common childhood infection, but thereof danger is underestimated in our country and around the world. About 800 thousand people get sick every year in the Russian Federation, half of whom are children 3–6 years old. In addition, for economic damage from infectious and parasitic diseases, varicella in the Russian Federation occupies 2–3 place for eleven years.Objectives. To substantiate the need to introduce varicella vaccine into the National immunization schedule of the Russian Federation based on the experience of introducing vaccination into regional schedules.Materials and Methods. The descriptive epidemiological method was used – a retrospective epidemiological analysis. Materials for the study were: Form № 2 «Information about infectious and parasitic diseases» for 2007–2017; State reports «On the state of sanitary and epidemiological welfare of the population in the Russian Federation» for 2016, 2017; scientific publications on the studied issue in Russian and English. The program «Microsoft Excel» was used to process the research data. Results. In regions in which varicella vaccination is introduced into regional immunization schedules, the incidence of infection tends to decrease at least to 3,1%, in contrast to regions where it is not introduced and there the incidence is increasing every year to 2,8%. The experience of using mass vaccination in other countries has shown its effectiveness, what is observed by decrease the incidence to a sporadic level.Discussion. The incidence of varicella in 2017 by region of the Russian Federation, where vaccination is included into regional immunization schedule, is 75% lower than the national average. Analysis of varicella vaccination introduction experience in other countries clearly shows that this method of combating varicella can significantly reduce the incidence, as well as reduce economic damage (US – 0.9 billion dollars, Japan – 36.2 billion yen).Conclusion. The vaccine prophylaxis of varicella clearly shows that this method of combating this infection can significantly reduce the incidence and at times reduce the economic damage from infection. With this in mind, the need to consider the inclusion of varicella vaccination in the Russian Federation National Schedule of Vaccinations.